Single nucleotide polymorphism of the Growth Hormone Receptor (GHR) encoding gene in Oryctolagus cuniculus - Gencheva, Deyana; Georgieva, Svetlana; Velikov, Krasimir; Koynarski, Tsvetoslav; Tanchev, Svetlin (Journal of BioScience and Biotechnology, 2018)
SINGLE NUCLEOTIDE POLYMORPHISM OF THE GROWTH HORMONE RECEPTOR (GHR) ENCODING GENE IN ORYCTOLAGUS CUNICULUS Deyana Gencheva1, Svetlana Georgieva1, Krasimir Velikov2, Tsvetoslav Koynarski3 and Svetlin Tanchev1 Authorsʼ addresses: 1Department of Genetics, Breeding and Reproduction, Faculty of Agriculture, Trakia University, 6000 Stara Zagora, Bulgaria 2Department of Special branches, Institute of Animal Science – Kostinbrod, 2232 Sofia, Bulgaria 3Department of General Livestock Breeding, Faculty of Veterinary Medicine, Trakia University, 6000 Stara Zagora, Bulgaria Correspondence: Deyana G. Gencheva Faculty of Agriculture, Trakia University 6000, Stara Zagora, Bulgaria Tel.+359 889 90 87 84 е-mail:dhristova@uni-sz.bg ABSTRACT Considered the rabbit Growth Hormone Receptor (GHR) gene as a candidate gene for growth efficiency, understanding the genetic variation in this locus is of particular relevance. The aim of the present research was to investigate populations from the rabbits (Oryctolagus cuniculus) and to identify single nucleotide polymorphism (SNP) with respect to the GHR gene through PCR-RFLP assay. Genotype profiles were established in a total of 100 rabbits from two populations (New Zealand White, NZW, n=51 and Californian, n=49), reared at The Institute of Animal Science, Kostinbrod. As expected, a 479bp amplicon of the polymorphic site (exon 3) of GHR gene was amplified using PCR and digested with endonuclease enzymes HinfI. The restriction pattern obtained in agarose gel electrophoresis was constituted by three bands (210bp, 162bp and 107 bp) for allele C and by two bands for allele G (317bp and 162 bp). The obtained restriction fragments revealed three genotypes: CC, CG and GG, observed in 7.8%, 53% and 39.2% of the NZW rabbit population and in 28.6%, 51% and 20.4% of the Californian rabbit population, respectively, without departure from the Hardy-Weinberg equilibrium (P>0.20) in the investigated groups. The allele frequencies determined a prevalence of the G allele (0.657) over the C allele (0. 343) in NZW rabbit population, while in the Californian rabbits, the frequency of the C allele (0.541) was higher than allele G (0.459). Observed heterozygosity was higher than expected, resulting in a negative inbreeding coefficient (Fis= -0.174 for NZW rabbits and Fis= -0.027 for Californian rabbits), indicating a sufficient number of heterozygous forms in both studied groups of rabbits. The obtained results from the present investigation confirmed the presence of the SNP in rabbit GHR gene. Therefore, the genetic variability established in this polymorphic locus could be applied in further association studies with growth traits in domestic rabbits. Key words: Oryctolagus cuniculus, Growth Hormone Receptor (GHR) gene, single nucleotide polymorphism (SNP), PCR-RFLP